(untitled) (CIPEEX, 2022)
THIS WORK ANALYZES THE PATH IN SEARCH OF THE LEGALIZATION OF PROSTITUTION AS A PROFESSION IN BRAZIL AND A BRIEF EXPOSITION OF THE TRAJECTORY OF THESE ATTEMPTS AT REGULATION. NOWADAYS, A POSITIVE RESPONSE HAS NOT YET BEEN OBTAINED FOR ANY OF THE ONSLAUGHTS THROUGH THE BILL. THIS SEARCH FOR SPECIFIC LEGISLATION FOR THE CATEGORY RANGES FROM EQUALITY AND JUSTICE IN THE PROFESSIONAL SCOPE, TO IMPROVEMENTS IN THE CONDITIONS OF EXERCISE AND SAFETY OF THIS ACTIVITY. WHAT HAS BEEN ACHIEVED OVER THE YEARS CANNOT BE UNDERESTIMATED, GIVEN THAT CONSERVATIVE SOCIETY IS RELUCTANT TO ACCEPT THIS ACTIVITY AS A PROFESSION.